2019
DOI: 10.52549/ijeei.v7i2.1047
|View full text |Cite
|
Sign up to set email alerts
|

A modified genetic algorithm with a new crossover mating scheme

Abstract: This study introduced the Inversed Bi-segmented Average Crossover (IBAX), a novel crossover operator that enhanced the offspring generation of the genetic algorithm (GA) for variable minimization and numerical optimization problems. An attempt to come up with a new mating scheme in generating new offspring under the crossover function through the novel IBAX operator has paved the way to a more efficient and optimized solution for variable minimization particularly on premature convergence problem using GA. A t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…In order to find an ideal solution to a problem in a complex space, it is necessary to find a compromise between two goals: to explore better solutions and to aggressively exploit the search space. Analytical studies have shown that GAs manage this trade-off optimally [7].…”
Section: Introductionmentioning
confidence: 99%
“…In order to find an ideal solution to a problem in a complex space, it is necessary to find a compromise between two goals: to explore better solutions and to aggressively exploit the search space. Analytical studies have shown that GAs manage this trade-off optimally [7].…”
Section: Introductionmentioning
confidence: 99%